TINGKAT PENDIDIKAN,JENIS KELAMIN,UMUR DAN STATUS PERKAWINAN TERHADAP KEPUTUSAN TENAGA KERJA - Gunawan Aji; Lutfi Ma’fu Azizah; Aisyah Aisyah; Zakiyah Mubarok; Muhammad Nabil (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The0purpose0ofithis study0is-to0look at how factors like education level, gender, age, and0marital status affect work choices. Work in the labor force is crucial to economic growth. According to data from the Central Statistics Agency (BPS), there were 143.72 million persons in the labor force as of August 2022, representing 68.63% of the population of working age. The findings ofithe0population0census,0which0is0conducted every0100years, were used to determine this number. This study employs the qualitative research design of a literature review. According to the research findings, the variable amount of education has a favorable impact on employment decisions, and the variable gender has0a favorable0and0substantial0impact0on employment.